GEOMARKETING ASPECTS OF SUSTAINABLE TOURISM (ON EXAMPLE OF NATIONAL NATURE PARK «SYNEVYR») - Igor Smyrnov (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2015)
Revealed geomarketing aspects of sustainable tourism on example of the National Nature Park «Synevyr» in Transcarpathian region of Ukraine. Submitted in comparison a classic version of the marketing mix (J. McCarthy), its alternative variant (author B.Loterbol) and author’s draft of the marketing mix in tourism. Shown the peculiarities of the structure and using of proposed by the author the marketing mix variant in the tourism industry on example of National Park «Synevyr».